2010
DOI: 10.5194/cp-6-345-2010
|View full text |Cite
|
Sign up to set email alerts
|

Millennial and sub-millennial scale climatic variations recorded in polar ice cores over the last glacial period

Abstract: Abstract. Since its discovery in Greenland ice cores, the millennial scale climatic variability of the last glacial period has been increasingly documented at all latitudes with studies focusing mainly on Marine Isotopic Stage 3 (MIS 3; 28-60 thousand of years before present, hereafter ka) and characterized by short Dansgaard-Oeschger (DO) events. Recent and new results obtained on the EPICA and NorthGRIP ice cores now precisely describe the rapid variations of Antarctic and Greenland temperature during MIS 5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
154
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 145 publications
(172 reference statements)
16
154
0
Order By: Relevance
“…7e), we see a considerable acceleration and an associated increase of abruptness 100 yr into the transition. This is in agreement with previous estimates of the abruptness of DO stadial-interstadial transitions in Greenland ice cores (∼ 125 yr) (Capron et al, 2010), although much higher rates were reported in atmospheric circulation proxies (Steffensen et al, 2008).…”
Section: Abruptness Of Stadial-interstadial Transitionssupporting
confidence: 82%
See 1 more Smart Citation
“…7e), we see a considerable acceleration and an associated increase of abruptness 100 yr into the transition. This is in agreement with previous estimates of the abruptness of DO stadial-interstadial transitions in Greenland ice cores (∼ 125 yr) (Capron et al, 2010), although much higher rates were reported in atmospheric circulation proxies (Steffensen et al, 2008).…”
Section: Abruptness Of Stadial-interstadial Transitionssupporting
confidence: 82%
“…This surprisingly fast adjustment can be attained by two processes: (i) wind changes in the Pacific (Timmermann et al, 2005b), and (ii) fast oceanic adjustment processes involving wave propagation from the Atlantic into the Indian and Pacific oceans, as discussed in Timmermann et al (2005a). The former can modulate the Indonesian Throughflow via the island rule (Godfrey, 1989), whereas the latter would have to change the joint effect of baroclinicity and relief (JEBAR) term in the barotropic transport equation (Sarkisyan and Ivanov, 1971;Cane et al, 1998). Irrespective of the relative magnitudes of these terms, our analysis clearly documents that the DO variability has far-reaching fast oceanic impacts that extend also into the other ocean basins.…”
Section: Abruptness Of Stadial-interstadial Transitionsmentioning
confidence: 99%
“…These fluctuations seem to resemble the short warming (precursor GI 23) and subsequent cooling events preceding GI 23 in the NorthGRIP and NALPS records (Fig. 7), which, however, are not included in the duration of GS 24 (Capron et al, 2010;Boch et al, 2011). MON 4 (Melisey 2) correlates with GS 22.…”
Section: Duration Of the Cold Spells Along The Transect From Greenlanmentioning
confidence: 99%
“…Besides the δ 18 O ice NorthGRIP ice core record, the U/Th-dated δ 18 O calcite speleothem record in the Northern Alps (NALPS) (Boch et al, 2011) provides a temperature-sensitive proxy record with resolution higher than 20 years and comparable to the NorthGRIP ice core. These two high-resolution archives show similar climate variability and reveal rapid temperature changes superimposed onto the millennial-scale variability (Capron et al, 2010;Boch et al, 2011). However, a detailed discussion about regional synchronicity is still hampered by the large dating uncertainty due to limitations in the chronologies.…”
Section: Introductionmentioning
confidence: 99%
“…Following the classical seesaw hypothesis (Stocker and Johnsen, 2003), inspired by Blunier and Brook (2001) using the Byrd and GISP2 ice cores and refined using the NorthGRIP-EDML synchronisation (Capron et al, 2010), the end of a Greenland Interstadial (GI) is contemporaneous with the onset of an Antarctic warming. The end of GI-20 in the GISP2 should thus correspond to the trough between Antarctic Isotope Maximums (AIM) 19 and 20 in the Vostok and EPICA Dome C isotope records.…”
Section: Glaciological Implicationsmentioning
confidence: 99%